Comprehensive global review and methodological framework for developing food atlases - Fallata, Ghadir; Alhadi, Rasil; Alnashmi, Luluh; Aljohani, Shahad; Alsaeed, Fatimah (Frontiers in Nutrition, 2024)
Introduction An atlas is a trustworthy resource created from precise data collection that serves as a guide for communities. A food atlas is a useful tool for analyzing dietary data. There is a growing need for a food atlas that is part of the nation’s strategy to help the health sector with specific nutritional or dietary assessments of individual consumption and overall wellbeing. Although researchers previously attempted to create a food atlas on a national level, the process of data collection was not well defined. Methods This study provides an overview of global food atlases that can be used to develop a procedure manual to guide experts in creating a dependable food atlas. Results To date, 27 countries have developed food atlases for various reasons. After examining these countries’ experiences, six important steps in the procedure manual that should be considered when developing a food atlas were identified: choosing the most consumed food, using traditional cooking utensils, determining portion sizes, capturing photographs of the food, validating the food atlas, and publishing the food atlas. Discussion This procedure manual can be used as a guide until a validation study is conducted.